2004
DOI: 10.1118/1.1755491
|View full text |Cite
|
Sign up to set email alerts
|

A procedure to determine the radiation isocenter size in a linear accelerator

Abstract: Measurement of radiation isocenter is a fundamental part of commissioning and quality assurance (QA) for a linear accelerator (linac). In this work we present an automated procedure for the analysis of the stars-shots employed in the radiation isocenter determination. Once the star-shot film has been developed and digitized, the resulting image is analyzed by scanning concentric circles centered around the intersection of the lasers that had been previously marked on the film. The center and the radius of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 10 publications
1
61
0
Order By: Relevance
“…The larger of the percentage or absolute value is taken as what is applicable. Measurements should be made for all clinically operable beamsAL11Commonly measured using a star shot technique,19 this test determines the diameter of the circle that intersects all rays formed by the projection of a narrow field as the collimator is rotated through an appropriate sample of angles within its full range of motion. The diameter must be within specificationsAL12This test determines the diameter of both the mechanical and the radiation isocenter defined by gantry rotation through its full clinical range of motion.…”
Section: Test Tablesmentioning
confidence: 99%
“…The larger of the percentage or absolute value is taken as what is applicable. Measurements should be made for all clinically operable beamsAL11Commonly measured using a star shot technique,19 this test determines the diameter of the circle that intersects all rays formed by the projection of a narrow field as the collimator is rotated through an appropriate sample of angles within its full range of motion. The diameter must be within specificationsAL12This test determines the diameter of both the mechanical and the radiation isocenter defined by gantry rotation through its full clinical range of motion.…”
Section: Test Tablesmentioning
confidence: 99%
“…In order to deliver successful stereotactic radiosurgery/radiotherapy treatments, it is essential to know the linac isocenter position, which is taken as the beam primary reference location ( 18 , 19 ) with submillimeter accuracy during several successive noncoplanar arcs, as well as its precise mechanical pattern during the gantry, collimator, and treatment table rotations. ( 11 , 13 , 20 – 22 ) …”
Section: Introductionmentioning
confidence: 99%
“…( 27 , 35 , 36 ) In ideal conditions, the mechanical isocenter is defined as the point of intersection of gantry, collimator, and treatment table rotation axes; ( 1 , 18 , 37 , 38 ) however, with the rotation of gantry, treatment table, and collimator, the isocenter also moves in the space due to the mechanical limitations of the linac components. ( 39 41 ) These limitations include gantry excursions during rotation due to its unbalanced weight which leads to bending or twisting of the gantry arm, ( 13 , 30 ) and irregularities that mainly originate from the precision bearing system of movement control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of this method depends on the determination of the center of the collimator slits based on the exposed film, as well as the jaw calibration, to ensure that the jaw opening is symmetrical about the rotational center of the gantry and collimator. With proper setup and analysis, previous authors have shown this test to be a viable option for determining radiation isocenter with the required accuracy 2 , 3 . The Winston‐Lutz test was originally intended for stereotactic radiosurgery (SRS) and uses a circulator collimator to image a small ball at a number of gantry and couch angles (4) .…”
Section: Introductionmentioning
confidence: 99%